Oral Syphilis: A Reemerging Infection Prompting Clinicians' Alertness - Sebastian Dybeck Udd; Bodil Lund (Hindawi Limited, 2016)
Syphilis is a rare but increasing disease. Due to changing sexual habits, presentation of oral manifestations may rise. Since syphilis may mimic other oral manifestations, diagnoses can be difficult. Clinicians need to be aware that ambiguous oral manifestations may in fact be caused by oral syphilis. Here, we present a case of extended diagnostic delay highlighting the importance of consulting an expert in infectious diseases in case of obscure oral lesions not responding to standard treatment. Despite seven visits to six different medical doctors, a patient who presented with oral syphilis was continuously misdiagnosed. After 6 months of increasing complaints and deteriorating severity of disease, the patient was referred to an oral and maxillofacial surgeon where the correct diagnosis was determined and proper treatment initiated.